Neuroactive Steroids in Acute Ischemic Stroke: Association with Cognitive, Functional, and Neurological Outcomes - Casas, Sebastian (2017)
Despite several scientific and technological advances, there is no single neuroprotective treatment that can reverse the brain damage after acute ischemic stroke (AIS). Neuroactive steroids are cholesterol-derived hormones that have the ability to modulate the normal and pathologic nervous system employing genomic and nongenomic mechanisms. In this work, we first investigated if AIS affects the plasma concentration of 5 neuroactive steroids (cortisol, estradiol, progesterone, testosterone, and 3α-androstenediol glucuronide). Second, we studied if levels of circulating steroids associate with neurological, cognitive, and functional outcome in a cohort of 60- to 90 year-old male and female patients with AIS. For this purpose, we recruited patients who were hospitalized at the Emergency Room of the Central Military Hospital within the first 24 h after stroke onset. We designed 2 experimental groups, each one composed of 30 control subjects and 30 AIS patients, both males and females. The assessment of neurological deficit was performed with the NIHSS and the tests used for the functional and cognitive status were: (1) modified Rankin Scale; (2) Photo test, and (3) abbreviated Pfeiffer's mental status questionnaire. We observed a significant difference in plasma concentration of cortisol and estradiol between both experimental groups. In the AIS group, higher levels of these neuroactive steroids were associated with more pronounced neurological, cognitive and functional deficits in women compared to men. We propose that in elderly patients, high levels of circulating neuroactive steroids like cortisol and estradiol could potentiate AIS-mediated neuropathology in the ischemic and penumbra areas.